THE EFFECT OF SERVICE QUALITY, PERCEIVED VALUE AND MEDIATING EFFECT OF BRAND IMAGE ON BRAND TRUST - Awalludin Fajar Brata Wijaya; Surachman Surachman; Mugiono Mugiono (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aimed to determine the effect of service quality on perceived value mediated by brand image and brand trust on the participant BPJS KESEHATAN Kesehatan Branch Malang (National Health Insurance Office Malang Branch). This study is using purposive sampling, 170 people who registered as social security administration's health Malang branch were selected as the respondents. All variables are measured by Likert scale. The Data was analyzed using partial least squares. The results are service quality influences significant ability to trust and brand image, and perceived value does not significantly influence trust, but significant influences brand image. Brand image partially mediates the effect of service quality on trust and fully mediates the effect of perceived value on trust. The implication of this research is social security administration health Malang branch must maintain and improve the quality of its services, promote and socialize to improve its brand image and brand trust.